Physical therapy for urinary incontinence in postmenopausal women with osteoporosis or low bone density: a randomized controlled trial. Issue 3 (March 2016) - Sran, Meena; Mercier, Joanie; Wilson, Penny; Lieblich, Pat; Dumoulin, Chantale
Abstract: Objective: To assess the effectiveness of 12 weekly physical therapy sessions for urinary incontinence (UI) compared with a control intervention, for reducing the number of UI episodes measured with the 7-day bladder diary, at 3 months and 1 year postrandomization. Methods: A single parallel-group randomized controlled trial was conducted at one outpatient public health center, in postmenopausal women aged 55 years and over with osteoporosis or low bone density and UI. Women were randomized to physical therapy (PT) for UI or osteoporosis education. The primary outcome measure was number of leakage episodes on the 7-day bladder diary, assessed at baseline, after treatment and at 1 year. The secondary outcome measures included the pad test and disease-specific quality of life and self-efficacy questionnaires assessed at the same timepoints. Results: Forty-eight women participated (24 per group). Two participants dropped out of each group and one participant was deceased before 3-month follow-up. Intention-to-treat analysis was undertaken. At 3 months and 1 year, there was a statistically significant difference in the number of leakage episodes on the 7-day bladder diary (3 mo: P  = 0.04; 1 y: P  = 0.01) in favor of the PT group. The effect size was 0.34 at 1 year. There were no harms reported. Conclusions: After a 12-week course of PT once per week for UI, PT group participants had a 75% reduction in weekly median number of leakage episodes, whereas the control group's condition had no improvement. At 1 year, the PT group participants maintained this improvement, whereas the control group's incontinence worsened.